2002
DOI: 10.1021/ar000194n
|View full text |Cite
|
Sign up to set email alerts
|

Masked o-Benzoquinones in Organic Synthesis

Abstract: An account of the synthetic utility of masked o-benzoquinones is provided. The inter- and intramolecular Diels-Alder reactions of in situ generated masked o-benzoquinones produced cycloadducts in excellent selectivities. New synthetic methodologies have been developed for the synthesis of highly substituted ring systems including bicyclo[2.2.2]octenones, oxatricycles, triquinanes, polysubstituted cyclohexanes, and bicyclo[4.2.2]decenones with complete stereocontrol from easily accessible 2-methoxyphenols via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(96 citation statements)
references
References 45 publications
3
93
0
Order By: Relevance
“…Recently, the reaction of "masked" ortho-benzoquinone [92] with C 60 was tested [93]. The [4+2] cycloaddition reaction of such electron-deficient dienes with fullerenes resulted in the formation of highly functionalized bicyclo[2.2.2] octenone-fused fullerenes.…”
Section: [4+2] Cycloadditionsmentioning
confidence: 99%
“…Recently, the reaction of "masked" ortho-benzoquinone [92] with C 60 was tested [93]. The [4+2] cycloaddition reaction of such electron-deficient dienes with fullerenes resulted in the formation of highly functionalized bicyclo[2.2.2] octenone-fused fullerenes.…”
Section: [4+2] Cycloadditionsmentioning
confidence: 99%
“…o-Benzoquinones are well known to react with nucleophiles following a 1,4-Michael addition reaction [1] or with diverse dienophiles performing a [4+2] cycloaddition [2,3]. Because most of o-benzoquinones are unstable (in contrast to p-benzoquinones), they are generally prepared in situ from their precursors, namely, catechols and 2-methoxyphenols [4].…”
Section: Introductionmentioning
confidence: 99%
“…5 By utilizing the Diels-Alder strategy of these MOBs, the total syntheses of several natural products have been accomplished. 5,6 Recently, we have demonstrated that the introduction of a bromo-substitution at the 4-position of 2-methoxyphenols, due to the increased thermal stability and reduced propensity of the resultant bromo masked o-benzoquinones to dimerize, provides the Diels-Alder adducts in higher chemical yields in comparison to non-bromo counterparts. 7 The total synthesis of a cis-clerodane diterpenic acid has been accomplished by making use of a bromo adduct 8 (Scheme I).…”
Section: Introductionmentioning
confidence: 99%